The hot-spot p53R172H mutant promotes formation of giant spermatogonia triggered by DNA damage - Xue, Y (Oncogene, 2017)
Overexpression of mutant p53 is a common finding in most cancers but testicular tumours accumulate wild-type p53 (wtp53). In contrast to the accepted concept that p53 homozygous mutant mice do not accumulate mutant p53 in normal cells, our study on a mutant p53 mouse model of Li-Fraumeni syndrome harbouring the hot-spot p53R172H mutation described an elevated level of mutant p53 in non-cancerous mouse tissues. Here we use detailed immunohistochemical analysis to document the expression of p53R172H in mouse testis. In developing and adult testes, p53R172H was expressed in gonocytes, type A, Int, B spermatogonia as well as in pre-Sertoli cells and Leydig cells but was undetectable in spermatocytes and spermatids. A similar staining pattern was demonstrated for wtp53. However, the intensity of wtp53 staining was generally weaker than that of p53R172H, which indicates that the expression of p53R172H can be a surrogate marker of p53 gene transcription. Comparing the responses of wtp53 and p53R172H to irradiation, we found persistent DNA double-strand breaks in p53R172H testes and the formation of giant spermatogonia (GSG) following persistent DNA damage in p53R172H and p53-null mice. Strikingly, we found that p53R172H promotes spontaneous formation of GSG in non-stressed p53R172H ageing mice. Two types of GSG: Viable and Degenerative GSG were defined. We elucidate the factors involved in the formation of GSG: the loss of p53 function is a requirement for the formation of GSG whereas DNA damage acts as a promoting trigger. The formation of GSG does not translate to higher efficacy of testicular tumorigenesis arising from mutant p53 cells, which might be due to the presence of delayed-onset of p53-independent apoptosis.